PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENIGKATKAN MOTIVASI DAN HASIL BELAJAR IPS MATERI PERISTIWA MENJELANG PROKLAMASI KEMERDEKAAN PADA SISWA KELAS V - Hasanah, Nenden Sri Ropiatul; Ece Sukmana; M.T Hartono Ikhsan (Sebelas April Elementary Education, 2024)
This research is based on the lack of enthusiasm of students in participating in the learning process so that their learning motivation is low and their involvement is very less. The results of this study were conducted in class V of SDN Sindang II social studies learning materials regarding the events leading up to the proclamation of independence. The method used in this research is the Classroom Action Research (CAR) method which adapts the Kemmis and Mc. Taggart by using a spiral system through stages starting from planning, action, observation, and reflection. The instruments used to collect data are learning motivation observation sheets and test sheets used to determine student learning outcomes. The purpose of implementing CAR by applying the role playing method is to improve motivation and learning outcomes. The results of data analysis obtained can be concluded that the use of role playing learning methods in social studies learning can increase student motivation and learning outcomes. This can be seen from the percentage increase in student learning motivation in the first cycle of 24%, the second cycle increasing to 72%, while the increase in student learning outcomes can be seen from the completeness of each cycle. The first cycle which completed 8 students was 32%, the second cycle which was completed by 25 students was 100%.